Multiscale Hemodynamics Using GPU Clusters (Communications in Computational Physics, 2012)
The parallel implementation of MUPHY, a concurrent multiscale code forlarge-scale hemodynamic simulations in anatomically realistic geometries, for multi-GPU platforms is presented. Performance tests show excellent results, with a nearlylinear parallel speed-up on up to 32GPUs and a more than tenfold GPU/CPU acceleration, all across the range of GPUs. The basic MUPHY scheme combines a hydrokinetic (Lattice Boltzmann) representation of the blood plasma, with a Particle Dynamics treatment of suspended biological bodies, such as red blood cells. To the best ofour knowledge, this represents the first effort in the direction of laying down general design principles for multiscale/physics parallel Particle Dynamics applicationsin non-ideal geometries. This configures the present multi-GPU version of MUPHY asone of the first examples of a high-performance parallel code for multiscale/physicsbiofluidic applications in realistically complex geometries.